2010
DOI: 10.1051/0004-6361/200912842
|View full text |Cite
|
Sign up to set email alerts
|

Mass loss from inhomogeneous hot star winds

Abstract: Context. The mass-loss rate is a key parameter of hot, massive stars. Small-scale inhomogeneities (clumping) in the winds of these stars are conventionally included in spectral analyses by assuming optically thin clumps, a void inter-clump medium, and a smooth velocity field. To reconcile investigations of different diagnostics (in particular, unsaturated UV resonance lines vs. H α /radio emission) within such models, a highly clumped wind with very low mass-loss rates needs to be invoked, where the resonance … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
149
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(162 citation statements)
references
References 40 publications
13
149
0
Order By: Relevance
“…Knowledge of the atmospheric structure allows the computation of the radiative forces; -recent developments in understanding the clumping properties of O stars have shown that porosity (and its effect on the velocity structure, called vorosity) could alter the shape of key diagnostic lines (e.g. Sundqvist et al 2010). Neglecting this effect could thus bias our determination.…”
Section: Wind Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge of the atmospheric structure allows the computation of the radiative forces; -recent developments in understanding the clumping properties of O stars have shown that porosity (and its effect on the velocity structure, called vorosity) could alter the shape of key diagnostic lines (e.g. Sundqvist et al 2010). Neglecting this effect could thus bias our determination.…”
Section: Wind Propertiesmentioning
confidence: 99%
“…Although theoretically expected (MacGregor et al 1979;Owocki & Rybicki 1984, 1985Runacres & Owocki 2002), clumping is currently not fully understood and characterized, although work is in progress (e.g. Puls et al 2006;Sundqvist et al 2010). This is a severe problem for stellar evolution since mass loss is a key parameter.…”
Section: Introductionmentioning
confidence: 99%
“…However, Sundqvist et al (2010) could not obtain satisfactory agreement between different diagnostics using the wind structure predicted by the current generation of radiation-hydrodynamics simulations of the LDI. Compared with these models, it appears that (a) structure must be initiated deeper in the wind; and (b) clumps need a greater internal velocity gradient.…”
Section: Structure In the Winds Of O-type Starsmentioning
confidence: 85%
“…This "porosity in velocity space" (dubbed "vorosity" by Owocki) is distinct from porosity in physical space, but also reduces the effective optical depth of the wind in different lines. In an impressive exploratory study, Sundqvist et al (2010) confirmed that both porosity (due to optically thick clumps) and vorosity (due to velocity gaps between clumps) play a…”
Section: The Origin and Nature Of Clumpingmentioning
confidence: 90%
See 1 more Smart Citation